The Structure of Matthew XIII - Wenham, David (New Testament studies, 1979)
The parable of the scribe trained for the kingdom of heaven Most commentators who have attempted to analyse the structure of Matthew xiii have argued that in this chapter the evangelist has deliberately brought together seven parables,1 seven being one of his favourite numbers. This view, however, deserves to be questioned, since, although it has often not been recognized as such, the saying about the scribe trained for the kingdom of heaven in υ. 52 was probably intended by Matthew to be regarded as a parable. He thus has eight parables, not seven.2